2022
DOI: 10.1088/1755-1315/1030/1/012004
|View full text |Cite
|
Sign up to set email alerts
|

Persea Americana Mill Extraction as Antibacteria

Abstract: Avocado leaves (P. americana ) are a part of plants that can be used as traditional medicines. Avocado leaves contain chemicals such as flavonoids, saponins, tannins and alkaloids which function as pathogenic antibacterial killer. This study aims to describe the antibacterial activity of various concentrations of avocado leaf extract (P. americana) on the growth of Escherichia coli. The extract concentrations were 25%, 50%, 75%, and 100%. This research employed experimental method with post-test group design. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…Oregano vulgaris extract contains active compounds such as alkaloids, flavonoids, tannins, and saponins that have antibacterial properties. The results of this research are consistent with those conducted by Wulandari et al, 10 which showed that saponins, alkaloids, and tannins in avocado leaves act as Gram-positive and Gram-negative antibacterials. The alkaloid inhibits the growth of recombinant S. aureus by disrupting the cell membrane of Gram-positive pathogenic bacteria.…”
Section: Resultssupporting
confidence: 92%
“…Oregano vulgaris extract contains active compounds such as alkaloids, flavonoids, tannins, and saponins that have antibacterial properties. The results of this research are consistent with those conducted by Wulandari et al, 10 which showed that saponins, alkaloids, and tannins in avocado leaves act as Gram-positive and Gram-negative antibacterials. The alkaloid inhibits the growth of recombinant S. aureus by disrupting the cell membrane of Gram-positive pathogenic bacteria.…”
Section: Resultssupporting
confidence: 92%